Implementation of the TGT Method and Puzzle Media in English Learning - Hanani, Muhammad Dzakir Aslam; Saputra, Nopran Riyan Agung; Fallo, Said Riztieo; Maslichah, Nora Ichdah; Dzakia, Salma Fauza; Islam, Ahmad Fakhruddin Fajrul (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
This study explores the implementation of the Team Games Tournament (TGT) method combined with puzzle media in the English learning process of the Teman Belajar tutoring program located in Bandung Village, Diwek Subdistrict, Jombang Regency. Initiated by students of Universitas Hasyim Asy’ari, this program specifically targets elementary school students (SD/MI) in rural areas to address limitations in traditional English instruction. Employing a qualitative descriptive approach, the research involved observation, interviews, and documentation to examine learning dynamics and student responses. The TGT method was applied through structured group activities that promoted cooperation, discussion, and tournament-style learning. Puzzle-based media were used to reinforce vocabulary and sentence construction in a visual and kinesthetic manner. Findings show that the integration of TGT and puzzle media significantly increased student motivation, participation, and English comprehension. Students became more engaged and confident, especially during game-based sessions that involved healthy competition and teamwork. Tutors observed notable improvements in vocabulary recall, pronunciation, and willingness to speak in English. The research concludes that the TGT method and puzzle media are effective and adaptable strategies for early English education in underserved areas. This study provides a model for community-based educational interventions that integrate collaborative and interactive learning to address foundational learning gaps.